UTOPIA AND DYSTOPIA IN THE MAP OF AMERICAN LITERATURE - Muhammad Kiki Wardana (BAHAS, 2018)
American literature shapes its narrative, form and ideology by the streams of historical events, political turmoil, land acquisition and conquest, civil wars and slavery. These very pivotal elements pertain to every theory or any literary criticisms that develop through time. Literature itself is timeless and universal but the birth of every literary criticism rejuvenates the perspective of preceding literary form itself. Utopia literature exposes the so called imagined perfect society where every realm of life is flawless. Utopia is just a notion of social depiction where high expectation is exercised and dreamt for. It is expressed as social critic at the same time where society at the time the utopia literature written is deteriorating or even crumbled. Dystopia, the derivative of Utopia sees it the other way around, it gives a reverse psychology consequence where everything is controlled and perfect would never be achieved. Dystopia criticizes Utopia for dreaming the dream of perfect society which the salient feature of dystopia against it. Dystopia gives us a clear understanding that our world in the future could be returned to the tyranny where the power of a nation relies on an evil leader. Dystopia seems relevant at the present even though it depicts the future society. Therefore, American literature embraces utopia and dystopia as American’s effigy of today’s life. The objective of this study is to trace, codify and comprehend the development of american’s utopia and dystopia literature through some works that have been written to present us a tangible map of the utopia and dystopia streams of literature.